2013
DOI: 10.5657/kfas.2013.0540
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition of Black Rockfish Sebastes schlegeli Fed on Diets Containing Different Levels of Turmeric Curcuma longa L.

Abstract: This study investigated the effect of diets supplemented with different levels (0, 1, 3, and 5 %) of turmeric Curcuma longa L. powder (TP) on the body composition of black rockfish Sebastes schlegeli. Fish weighing 10.05±0.44 g were fed to apparent satiation twice daily for 8 weeks. Adding TP decreased crude lipid levels and increased crude protein and ash levels. Abundant fatty acids in the TP-added group were C16:0, C18:1 n-9 (cis), and C22:6 n-3. The major amino acids in samples were glutamic acid, aspartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 9 publications
7
9
0
Order By: Relevance
“…On the contrary, Pham et al (2014) having fed paprika to Paralichthys olivaceus observed insignificant differences in the content of C14:0. For the same results also reported Hwang et al (2013) for Sebastes schlegeli fed with different curcumin levels. According to Lee et al (2012), the supplementation of garlic led to statistically lower amount of C14:0 in the meat of Acipenser ruthenus.…”
Section: Fatty Acid Compositionsupporting
confidence: 71%
See 4 more Smart Citations
“…On the contrary, Pham et al (2014) having fed paprika to Paralichthys olivaceus observed insignificant differences in the content of C14:0. For the same results also reported Hwang et al (2013) for Sebastes schlegeli fed with different curcumin levels. According to Lee et al (2012), the supplementation of garlic led to statistically lower amount of C14:0 in the meat of Acipenser ruthenus.…”
Section: Fatty Acid Compositionsupporting
confidence: 71%
“…On the contrary, Farahi et al (2010) observed the highest amount of ash in Oncorhynchus mykiss as a result of added garlic in the feed. For the same also reported Hwang et al (2013) who studied the effect of paprika supplementation on the ash content in the fillets of Sebastes schlegeli. The inclusion of thyme also tended to increase the ash content in Oreochromis niloticus (Antache et al, 2013).…”
Section: Chemical Compositionmentioning
confidence: 68%
See 3 more Smart Citations